The thiol-isocyanate click reaction: Facile and quantitative access to ?-end-functional poly(N,N-diethylacrylamide) synthesized by RAFT radical polymerization - Li, H.; Yu, B.; Matsushima, H.; Hoyle, C.; Lowe, Andrew (American Chemical Society, 2009)
N,N-Diethylacrylamide (DEAm) was homopolymerized by reversible addition-fragmentation chain transfer (RAFT) radical polymerization yielding a homopolymer with a calculated degree of polymerization of 30 (PDEAm 30), as determined by 1H NMR spectroscopic end-group analysis, and a polydispersity index (Mw/Mn) of 1.10. Aminolysis of the dithioester end groups followed by treatment with tris(carboxyethyl)phosphine hydrochloride yielded the corresponding macromolecular secondary thiol (PDEAm3O-SH). Reaction of PDEAm 30-SH with a range of commercially available isocyanates, catalyzed by NEt3, gave the corresponding thiocarbamate end-functional polymers in essentially quantitative yield as determined by a combination of 1H NMR spectroscopy and UV-vis spectrophotometry. These reactions were shown to be rapid as evidenced by the real-time kinetics for the reaction between PDEAm30-SH and hexyl isocyanate in the presence of NEt 3. Additionally, these facile reactions were shown to proceed without any apparent detrimental effect/side reactions to the basic polymer structure as evidenced by size exclusion chromatography with all modified polymers retaining their narrow molecular weight distributions. The lower critical solution temperatures (LCSTs) of the resulting cu-modified PDEAm homopolymers were evaluated by turbidimetry. For those samples that were soluble in aqueous media the measured LCSTs were between 3 and 11°C lower than that determined for PDEAm30-SH (34°C). Such differences were attributed to the hydrophobic nature of the newly introduced end groups-the effect being pronounced given the relatively low molecular weight of the precursor homopolymer. In two instances, and specifically the end-modified PDEAm homopolymers obtained from reaction with 9-isocyanato-9H-fluorene and 4-(2-isocyanatoethyl)biphenyl, the resulting materials were not soluble in water even at temperatures approaching 0°C. © 2009 American Chemical Society.